The influence of defect and temperature on the fatigue behaviours of Al‐Si‐Cu‐Mg‐Ni alloy. Issue 10 (15th July 2019) - Liu, Haiquan; Pang, Jianchao; Wang, Meng; Li, Jianping; Guo, Yongchun; Li, Shouxin; Zhang, Zhefeng
Abstract: High‐cycle fatigue (HCF) properties of two Al‐Si‐Cu‐Mg‐Ni alloys with different defect sizes named as alloys A (smaller ones) and B (bigger ones) were investigated at 350°C and 425°C, respectively. The results indicate that fatigue strengths of both alloys decrease as the temperature increases. Fatigue cracks originated from pores and oxide films at both temperatures. They propagated preferentially through cracked matrix at 350°C and debonded interface and grain boundary at 425°C. Alloy A exhibits higher fatigue life and fatigue strength than alloy B at 350°C due to its smaller pore sizes. However, it has slightly worse fatigue properties than alloy B at 425°C because the fatigue crack initiation is controlled by oxide film at this temperature and is not affected by its size. This indicates that there is a transition of predominant initiation site from pores to oxide films when the temperature increases. The fatigue strength estimated through defect size is consistent with the experimental results at 350°C, while unsuitable at 425°C.